Pathways to and Results of Psychiatric Consultation for Patients Referred from the Emergency Department. Are there Differences between Migrant and Native Patients?. (February 2019) - Gramaglia, Carla; Gambaro, Eleonora; Delicato, Claudia; Di Marco, Sarah; Di Tullio, Elisa; Vecchi, Camilla; Bert, Fabrizio; Castello, Luigi Mario; Siliquini, Roberta; Avanzi, Giancarlo; Zeppegno, Patrizia
The aim of this study was to compare migrants and native Italians on the pathways to care and results of psychiatric consultation (PC) in the emergency department (ED). Patients who were referred from the ED for psychiatric consultation (EDPC) at the Maggiore della Carità Hospital between March 2008 and March 2015 were recruited consecutively. Socio-demographic, clinical and consultation variables were recorded along with information about suicidal behaviours; migrants ( n = 379; 42.74% males, 57.26% females; age: 45.38 ± 16.95 years) were compared with native Italians ( n = 2942; 43.51% males, 56.49% females; age: 42.08 ± 15.89 years). Migrants were younger, more likely to be unemployed and less likely to be already under the care of a psychiatrist. Symptoms related to use of alcohol or substances were more frequent in migrants, especially female migrants. Migrants were less likely than native Italians to be referred for PC because of the presence of psychiatric symptoms, however they were more likely to be referred because of self-harming behaviour. Nonetheless, migrant status was not identified as a risk factor for suicidal behaviour in the multivariate analysis. The outcome of EDPC showed differences between migrants and natives. In absolute terms migrants were less likely to be admitted to a psychiatric ward after the EDPC than native Italians, while they were more likely to be monitored in the ED before being discharged or referred to outpatient care. In a high percentage of psychiatric examinations of migrants, no psychiatric symptoms were identified. Further studies are warranted to disentangle the meaning of these findings.